2022
DOI: 10.1039/d1py01380g
|View full text |Cite
|
Sign up to set email alerts
|

From gas separation to ion transport in the cavity of hyperbranched polyamides based on triptycene aimed for electrochromic and memory devices

Abstract: With the aim to obtain robust electrochemical cycling stability which is crucial for application of smart electrochromic devices (ECD), we propose an effect strategy by introducing three-dimensional (3D) star-shaped triptycene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Figure S22 shows the typical CV curves of PAs, which undergo two quasi-reversible single-electron oxidation–reduction processes, which are due to the presence of two N atoms as redox center in a single link of the polymer. , Specifically, the two oxidation processes of PAs could be attributed to the successive removal of one electron from the BPT unit and the TPA group . It is worth noting that the first ( E 1/2 = 0.68, 0.71, and 0.68 V (sequence: CA, 6F, and OA)) oxidation potential of TPA-7-BPT series PAs is higher than that of TPA-12-BPT series PAs ( E 1/2 = 0.44, 0.62, and 0.54 V (sequence: CA, 6F, and OA)).…”
Section: Resultsmentioning
confidence: 99%
“…Figure S22 shows the typical CV curves of PAs, which undergo two quasi-reversible single-electron oxidation–reduction processes, which are due to the presence of two N atoms as redox center in a single link of the polymer. , Specifically, the two oxidation processes of PAs could be attributed to the successive removal of one electron from the BPT unit and the TPA group . It is worth noting that the first ( E 1/2 = 0.68, 0.71, and 0.68 V (sequence: CA, 6F, and OA)) oxidation potential of TPA-7-BPT series PAs is higher than that of TPA-12-BPT series PAs ( E 1/2 = 0.44, 0.62, and 0.54 V (sequence: CA, 6F, and OA)).…”
Section: Resultsmentioning
confidence: 99%
“…Polyamide electrochromic materials are the most widely studied materials in SECPs [ 25 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. The performance comparison of PA–ECPs is listed in Table 3 .…”
Section: Special Engineering Plastic-based Electrochromic Polymers (S...mentioning
confidence: 99%
“…Organic materials such as conducting polymers and viologens have recently become an intensive research topic. The conducting polymers have several advantages over inorganic compounds as EC materials, including good electrochemical stability, fast switching speed, high coloring efficiency (CE), easy large-area processing, and color tuning through chemical modification. Also, triphenylamine (TPA)-containing polymers have been developed as an attractive family of EC materials because of their colorless neutral state and intriguing EC behaviors. In recent years, redox-active materials with optical absorption change in the near IR (NIR) region have drawn significant attention due to their potential applications in optical communication, data storage, and thermal control in buildings and spacecraft. , For example, Wan et al reported that the quinone-containing EC materials revealed high absorption in NIR upon electrochemical reduction . Reynolds and Beaujuge reported that the conjugated polymers could exhibit multicolor in the neutral state and transmission in the oxidized state. , Liou and Lin also noted that the TPA-based polymers demonstrated an attractive anodic EC system for NIR applications due to their particular intramolecular electron transfer in the oxidized forms …”
Section: Introductionmentioning
confidence: 99%